Synthesis of Schiff Base Complexes and Study their Applications as Catalysts for Esterification of Acetic Acid - Almadani, Enas A; Ibrahim, Dalal M; Saleh, Sara A (Iraqi Journal of Science, 2025)
Schiff bases and their metal complexes have been found to exhibit high catalytic activity in a wide range of organic reactions, and their stability in the presence of moisture and high temperatures makes them particularly useful as catalysts in reactions that require elevated temperatures. In this study, new Schiff base (L) 2-((3-nitrophenylimino) methyl) phenol and new copper (II) and cobalt (II) complexes were synthesized from 3-nitrophenylamine with salicylaldehyde. The complexes were prepared by weighing the metal chloride and dissolved in methanol. The synthesised samples were characterized by FT-IR, UV-vis, SEM, and EDX and tested for catalytic activity as homogenous catalysts for esterification reactions. The free ligand's υ(C=N) stretching vibration was verified by the peak in the FT-IR spectra. The shift of this band to a lower frequency in the metal complexes' spectra, indicates that azomethine nitrogen participated in the coordination of metal ions in comparison to the parent ligand, metal complexes displayed a porous area, which might result from the ligand's cooperative contribution to the voids contracting for the metal ions to cause complications. The SEM image of the Schiff base had a surface morphology that was non-uniform, spherical, and crystalline. Synthesised catalysts were able to give the highest acid conversions of up to 77% since transition elements have the highest oxidation state when combined with Schiff bases, which also increase their Lewis acidity relative to the ligand. The esterification of acetic acid with ethanol using Co-complex at 80 oC during the three hours of reaction time showed the highest acid conversions of 77%, and the conversion ratio using the Cu-complex was 76% at the same conditions, while the acid conversions without catalysts and with the ligand were 63.4% and 70.2%, respectively.